(5 цілих 44/47-x) + 4 цілих 23/47 = 6 цілих 1/47

(5 цілих 44/47-x) + 4 цілих 23/47 = 6 цілих 1/47

  • (5 44/47-x) +4 23/47 = 6 1/47
    5 44/47-x = 6 1 / 47-4 23/47
    5 44/47-x = 1 25/47
    X = 5 44 / 47-1 25/47
    X = 4 19/47
  • 5 + 44/47-X + 4 + 23/47 = 6 + 1/47
    X = 5 + 44/47 + 4 + 23 / 47-6-1 / 47
    X = (5 + 4-6) + (44 + 23-1) / 47 = 3 66/47 = 4 19/47

Понравилась статья? Поделись с друзьями:
Добавить комментарий

;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

65 − 58 =